Assessing Teachers’ Social Emotional Competence: A Systematic Review - Oktarina, Nina; Kurniawati, Farida (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
A review of the literature on the assessment of teachers' social-emotional competence (SEC) was conducted to ascertain its role in enhancing education quality and student outcomes. A total of 2,905 records were screened according to the PRISMA guidelines, and 15 studies that utilized instruments such as SECTRS, EduSEL-R, TSELCS-22, ESELC, and SASEIC Questionnaire within the Prosocial Classroom Model framework were included in the review. The results indicate that these tools effectively assess SEC dimensions, particularly in fostering positive teacher-student relationships, classroom management, and SEL program implementation. However, significant challenges remain, including cultural bias, reliance on self-reports, and limited validation across diverse contexts. Practical implications suggest that these assessments can guide professional development, enhance teacher well-being, and improve classroom environments, ultimately supporting students' academic and emotional growth. Future research should focus on developing culturally responsive, validated instruments that reduce administrative burden while capturing the multifaceted nature of SEC in real-world educational settings.